The Mohorovičić discontinuity beneath the continental crust: An overview of seismic constraints - Carbonell, Ramon; Levander, Alan; Kind, Rainer (Tectonophysics, 2013)
The seismic signature of the Moho from which geologic and tectonic evolution hypotheses are derived is to a large degree a result of the seismic methodology which has been used to obtain the image. Seismic data of different types, passive source (earthquake) broad-band recordings, and controlled source seismic refraction, densely recorded wide-angle deep seismic reflection, and normal incidence reflection (using VibroseisTM, explosives, or airguns), have contributed to the description of the Moho as a relatively complex transition zone. Of critical importance for the quality and resolution of the seismic image are the acquisition parameters, used in the imaging experiments. A variety of signatures have been obtained for the Moho at different scales generally dependent upon bandwidth of the seismic source. This variety prevents the development of a single universally applicable interpretation. In this way source frequency content, and source and sensor spacing determine the vertical and lateral resolution of the images, respectively. In most cases the different seismic probes provide complementary data that gives a fuller picture of the physical structure of the Moho, and its relationship to a petrologic crust–mantle transition. In regional seismic studies carried out using passive source recordings the Moho is a relatively well defined structure with marked lateral continuity. The characteristics of this boundary change depending on the geology and tectonic evolution of the targeted area. Refraction and wide-angle studies suggest the Moho to be often a relatively sharp velocity contrast, whereas the Moho in coincident high quality seismic reflection images is often seen as the abrupt downward decrease in seismic reflectivity. The origin of the Moho and its relation to the crust–mantle boundary is probably better constrained by careful analysis of its internal details, which can be complex and geographically varied. Unlike the oceanic Moho which is formed in a relatively simple, well understood process, the continental Moho can be subject to an extensive variety of tectonic processes, making overarching conclusions about the continental Moho difficult. Speaking very broadly: 1) In orogenic belts still undergoing compression and active continental volcanic arcs, the Moho evolves with the mountain belt, 2) In collapsed Phanerozoic orogenic belts the Moho under the collapse structure was formed during the collapse, often by a combination of processes. 3) In regions having experienced widespread basaltic volcanism, the Moho can result from underplated basalt and basaltic residuum. In Precambrian terranes the Moho may be as ancient as the formation of the crust, in others Precambrian tectonic and magmatic processes have reset it. We note that seismic reflection data in Phanerosoic orogens as well as from Precambrian cratonic terranes often show thrust type structures extending as deep as the Moho, and suggest that even where crust and mantle xenoliths provide similar age of formation dates, the crust may be semi-allochothonous.